Penerapan Model Pembelajaran Kooperatif Tipe Number Head Together (NHT) Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Masa Kejayaan Islam Kelas XI di SMA Negeri 1 Samadua - Saffan, Edi (Jurnal Ikhtibar Nusantara, 2022)
This study was motivated by the low learning outcomes of students in class XI-A at SMA Negeri 1 Samadua. The low learning outcomes were caused by various factors, including teachers still using conventional methods and teacher dominance in the learning process, resulting in an ineffective and monotonous learning process. This study aimed to improve student learning outcomes by using the Number Head Together learning model in class XI-A at SMA Negeri 1 Samadua. This study is a Classroom Action Research (CAR). This research was conducted in two cycles. The subjects of this research were 26 students of class XI-A of SMA Negeri 1 Samadua, who were selected through total sampling. The data collection techniques used in this research were observation, questionnaires, and tests. The data were analyzed using percentage statistical formulas. The results of the research showed an increase in student learning outcomes. In the pre-cycle, the percentage of student learning achievement was only 46.15% with an average score of 63.46. In cycle I, it increased to 69.23% with an average score of 68.85, and in cycle II, there was a more significant increase to 88.46% with an average score of 78.46%. Student learning activities also improved from the category of adequate (C) to good (B), and the category of good increased to very good (A). Student responses to the implementation of the Number Head Together model used by teachers in PAI learning were positive. This can be proven by the students' response, with an average of 85% agreeing and only 15% disagreeing. Finally, the application of the Number Head Together learning model can improve the learning outcomes of students in class XI-A at SMA Negeri 1 Samadua.